Databook of flame retardants - Wypych, Anna; Wypych, George (ChemTec Publishing, 2021)
"The major application of flame retardants is in products used at home (furnishings, appliances, upholstery, carpets, curtains, fabrics, etc.), electronic and electrical devices, (computers, TV sets, phones, wiring, etc.), building construction materials, and transportation products (cars, airplanes, railroad equipment, etc.)."-- Provided by publisher.
Keywords: Fireproofing agents.; elektronické knihy; electronic books